Assessment of the Education Environment of the Saudi Board of Family medicine, KSA. 2020 - Binyamin, Sultana; Mandoura, Najlaa; Ibrahim, Adel (American Journal of Education and Practice, 2021)
Background: Competent educational environment for medical postgraduate is crucial to ensure sound clinical outcome. The quality of the educational environment is influenced by many factors, physical, social and intellectual. The current study aimed at assessing the educational environment in a postgraduate Saudi Board for Family Medicine in Jeddah. Methodology: Through cross sectional study design, all residents in the Saudi Board of Family medicine in Jeddah were invited to participate in the study; they were asked to fill a predesigned adopted valid questionnaire based on the Scan of Postgraduate Educational Environment Domain (SPEED) which is used to assess the quality of the Post Graduate Medical Education. Data were collected during gathering of the residents in a usual didactic teaching day. A total of 186 residents responded, making a response rate 93%. Results: Out of all participants (n=186), females formed two thirds of the residents (60.8%), their mean age was 27.6±2.27 years, with an almost equal representation of the four residency levels. The highest scores about the quality of the educational process was observed in the item regarding the supervisors being respectful towards the registrars (mean score 4.1 out of 5), followed by the being approachable and helpful (mean score 4.0). The lowest scores were observed regarding presence of staff in general who have positive impact on the educational environment (mean score 3.2), followed by availability of good clinical supervisors all the time (mean score 3.3). The overall mean score accounted for 3.6± 0.56, although it was higher in females (3.7±0.642) than males (3.5±0.661), and in those in R1 (3.7±0.509) and R4 (3.7±0.605), however, these differences are not statistically significant p>0.05. Also, no statistically significant correlation between and age and overall mean score was observed. Conclusion and recommendations: The Saudi Board residents for Family Medicine considered their educational environment as more positive than negative with potential areas for improvement. Although females perceived the educational environment better than male trainees, no significant changes observed along the different stages of the program. It is recommended to use these findings in reforming the educational environment in the Saudi Board.